The Sjögren’s syndrome – an interdisciplinary problem viewed by a dentist - Agata Barczyk; Sebastian Foryś (Rheumatology, 2014)
Sjögren’s syndrome is common and chronic disease. So far there is no effective therapy. In 90% of cases, it affects women, usually in the peri-menopausal period. Many systems and organs may be involved in the course of the disease, thus it is interesting for many medical specialists. There are primary and secondary Sjögren’s syndromes, both characterized mainly by xerostomia and keratoconjunctivitis. The paper reviews basic symptoms in the oral cavity involving the oral mucosa, lips, tongue, gingiva, teeth and periodontium. Treatment and prevention in a dental clinic are also described. Lifestyle and pharmacotherapy to avoid symptom aggravation are additionally considered.